Effects of Aerobic Exercise on Lipid Profile in Patients with Type 2 Diabetes (NIDDM) (Medical Forum Monthly, 2024)
Objectives: This study was undertaken to observe the effects of aerobic exercise on lipid profile in newly diagnosed type 2 diabetic patients.Study Design: Observational studyPlace and Duration of Study: This study was conducted at Physiology Department, JPMC Karachi from December 2001 to May 2002.Materials and Methods: 30 adult male subjects with uncomplicated type 2 diabetes were selected from diabetic clinic of JPMC, Karachi. 30 apparently healthy adult male subjects were selected from friends, students and staff members of BMSI, as control. The subjects belonging to diabetic groups were then briefed about exercise protocol, which consisted of a regular brisk walk of 30 minutes on alternate days per week for 60 days.Results: Base line Values of mean HDL-cholesterol serum cholesterol, serum total triglycerides, LDL- cholesterol, and mean fasting blood glucose were significantly different in diabetic group as compared to control group (P<0.001) After aerobic exercise, all the parameters except HDL-C were significantly decreased while HDL-C was significantly increased as compared to the pre-exercise values. Conclusion: Regular aerobic exercises improve blood glucose, TAG, LDLc and cholesterol and increases the HDLc in type 2 diabetic subjects has been concluded by the present study.